Grid chaotic attractors based on arc tangent and its secure communication - Xue-zhi MAO; Yong XU; Jian-ping LIU; Hui-quan MA (Tongxin xuebao)
A smooth arc tangent function series approach for creating multi-directional multi-scroll grid chaotic attractors was proposed,including one-directional n-scroll,two-directional n×m-grid scroll,and three-directional n×m×l-grid scroll chaotic attractors.The chotic properties were studied by equilibrium points analysis,numerical simulation,Lyapunov exponents spectrum,bifurcation diagrams and Poincaré section diagrams.Synchronize the two grid multi-scroll chaotic systems with same structure by designing simple linear feedback control lows,which is applied to secure communication.The effectiveness of this method has been verified by simple analysis and numerical simulation.